Contributing to the construction of a framework for improved gender integration into climate-smart agriculture projects monitoring and evaluation: MAP-Norway experience - Gutiérrez Montes, Isabel A. (2018)
Abstract TheMesoamerican Agroenvironmental Program (MAP-Norway) is a multi-dimensional rural development program implemented in Central America since 2009, working with smallholder families, producer organizations, governmental organizations, and regional governance platforms. To monitor, assess, and evaluate the effects of the program on its beneficiaries, MAP-Norway uses a series of indicators that allow project managers and donors to adapt and follow-up on the interventions. Because gender is a cross-cutting theme in the program, gender indicators are used at all levels: families, producer organizations, and governmental organizations and governance platforms. In this document, we use the experience of MAP-Norway to critically assess these indicators, considering their potential usability in the monitoring and evaluation of climate-smart agriculture (CSA) initiatives. Furthermore, we propose a series of other indicators that capture various dimensions of gender relations. These indicators can be used to assess the effect of CSA practices, services, and technologies on equity in decision-making, women’s empowerment (including economic empowerment), intra-household food security, and equity in ownership over productive resources, among others, thus providing evidence that can help better design and target CSA interventions.